(untitled) (International Journal of Food and Nutritional Sciences, 2022)
One of the most important technological developments in additive manufacturing that has been adopted and accepted as a component of the contemporary industry is 3D printing. It offers several advantages over traditional approaches, with time being one of the most important. Typically, in additive manufacturing processes, the element is produced using the principles of rapid prototyping of the material, as well as layer-by-layer deposition, which is accomplished by transferring the information to the machine’s software. Which uses Stereo Lithography (STL) file. Format created by modeling software (CAD). These days, the use of 3D printing in mechanical engineering is particularly beneficial for research and invention of a variety of components, from simple, everyday use structures to complicated ones. Simple, dependable, or precise are a few advantages that 3D printing provides for components employed in aerospace applications, making it one of the most well-liked ways to make concepts-only parts. 3D printing is becoming the most widely used additive manufacturing technology across all industries, not only engineering. The main objective of this paper is to learn more about 3D printing and its application.